REVOLUTIONIZING HEALTHCARE: THE IMPACT OF ARTIFICIAL INTELLIGENCE ON PATIENT CARE, DIAGNOSIS, AND TREATMENT - Ashish Shiwlani; Murad Khan; Abdul Mannan Khan Sherani; Muhammad Umer Qayyum; Hafiz Khawar Hussain (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
This article provides a comprehensive exploration of the profound impact of Artificial Intelligence (AI) on the healthcare industry. It begins by elucidating AI's pivotal role in disease detection, diagnostics, and personalized treatment. The discussion unveils the enhanced diagnostic capabilities driven by AI algorithms, marking a paradigm shift towards more accurate and efficient treatment strategies. The second segment delves into the multifaceted ways AI influences patient outcomes, ranging from predictive analytics to therapy optimization. The third part offers insights into the transformative potential of AI in reshaping patient care, preventative medicine, and personalized healthcare. Subsequent sections explore smart healthcare, innovative solutions, the synergy of technology and medicine, disease detection and prevention, and the full spectrum of AI applications in healthcare. The article concludes by highlighting the revolutionary potential of AI in healthcare, acknowledging challenges such as data privacy and ethical concerns. The partnership between AI and healthcare promises a future marked by patient-centric, technologically advanced healthcare, paving the way for improved outcomes, efficiency, and tailored medicine.